Patterns of infectious complications and their implication on health system costs after esophagectomy for esophageal cancer: real-world data from three European centers - Ledda, Anna Lucia; Tarantino, Ignazio; Schiefer, Sabine; Ronellenfitsch, Ulrich; Gomes dos Santos Ferreira Rebelo, Artur Luis; Sekulla, Carsten; Nienhüser, Henrik; Michalski, Christoph; Schmied, Bruno; Kleeff, Jörg H.; Klose, Johannes (Langenbeck's archives of surgery, 2025)
Purpose: Infectious complications occur frequently after esophagectomy leading to prolonged hospital stay and increased costs. This study aimed to analyze the pattern of infectious complications, the spectrum of associated microbiota, and its impact on health system costs in patients who underwent esophagectomy for esophageal cancer. Methods: All patients undergoing curative resection for histologically confirmed esophageal cancer between January 2017 and August 2022 were included. Patients’ survival was analyzed by Kaplan–Meier estimate. Contingency tables were applied to assess the association between microbiota and the occurrence of infectious complications and their impact on patients’ survival. Results: Four hundred forty-one patients who received a R0 resection for esophageal cancer were identified. Infectious complications occurred in 153 patients (34.7%). Pneumonia was the most frequent complication (28.8%) followed by anastomotic leakage (25.4%). Enterococcus and Candida species were the dominant microbiota associated with infectious complications (Candida species: OR 7.34, 95% CI 2.38–22.67) and anastomotic leakage (Enterococcus species: OR 6,15, 95% CI 1,51–24,99; Candida species: OR 7.14, 95% CI 2.48–20.56). Intensive care unit stay (mean 14.3 vs. 4.9 days, p < 0.001) and total hospital stay (mean 34.1 vs. 18.8 days, p < 0.001) were significantly longer in patients with infectious complications. Total health system costs (44.084 € vs. 25.907 €) increased after the occurrence of infectious complications. Conclusion: Infectious complications after esophagectomy are predominantly associated with the presence of Enterococcus and Candida species, leading to increased health system costs. Preventive antibiotic and antimycotic treatment might result in reduction of infectious complications and lower health system costs.
Veröffentlicht: 22. April 2025
Gesehen am 29.09.2025